2006
DOI: 10.1016/j.jmaa.2005.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Browder spectra of upper-triangular operator matrices

Abstract: Let M C = A C 0 B be a 2 × 2 upper triangular operator matrix acting on the Hilbert space H ⊕ K. In this paper, for given operators A and B, we prove thatthe Browder resolvent of an operator T and C∈B(K,H) σ (M C ) has been determined in [H.K. Du, P. Jin, Perturbation of spectrums of 2 × 2 operator matrices, Proc. Amer. Math. Soc. 121 (1994) 761-776]. Moreover, we explore the relations of σ (A) ∪ σ (B) \ σ (M C ), σ b (A) ∪ σ b (B) \ σ b (M C ) and σ w (A) ∪ σ w (B) \ σ w (M C ), where σ (A), σ b (A) and σ w (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One way to study operators is to see them as entries of simpler operators. The operator matrices have been studied by numerous authors [1][2][3][4][5][6][7][8][9][10][11][12][13]. This paper is concerned with the semi-Fredholmness of 2 × 2 operator matrices.…”
Section: Introductionmentioning
confidence: 99%
“…One way to study operators is to see them as entries of simpler operators. The operator matrices have been studied by numerous authors [1][2][3][4][5][6][7][8][9][10][11][12][13]. This paper is concerned with the semi-Fredholmness of 2 × 2 operator matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for T ∈ B(H), we introduce its corresponding spectra as following [19]: Moreover, it has been proved that s mul(T ), b.s. mul(T ) ∈ {0, 1, 2, .…”
mentioning
confidence: 99%
“…(K, H) σ sb (M C ) and C∈B(K, H) σ b (M C ) completely, where M C = is a 2 × 2 upper triangular operator matrix defined on H ⊕ K. For the study advances of 2 × 2 upper triangular operatormatrix, see ([1][2][3][4],[13][14][15][16][17][18][19]). …”
mentioning
confidence: 99%
“…In[2], Zhang and Du found that formula (12) used in their proofs of Theorem 4 in[1] is not always true and proposed an additional condition to fill this gap. However, there is another gap in the proof of Theorem 4 in[1], that is, the claim in line 17 on p. 705 is not always true.…”
mentioning
confidence: 99%
“…However, there is another gap in the proof of Theorem 4 in[1], that is, the claim in line 17 on p. 705 is not always true. It seems that this claim had not been corrected by the authors, but the additional condition in[2] can also fill this gap, in fact, if iso(∂Λ (A,B)) = φ, then W 3 (A, B, C ) = W 1(A, B, C ).…”
mentioning
confidence: 99%